The impact of Filifactor alocis on the severity of periodontitis among diabetic and non-diabetic patients: a narrative review - Manenzhe, Shumani Charlotte; Koutras, Sandra; Zwane, Nompumelelo Benedicta; Masilana, Aubrey Isaac; Shangase, Sindisiwe Londiwe (Frontiers in Dental Medicine, 2024)
The extensive studies on Filifactor alocis (Fa) show a positive association with periodontitis, demonstrating elevated Fa levels compared to traditional periodontal pathogens in severe disease. Periodontitis is a chronic multifactorial disease induced by a dysbiotic microbiota in a susceptible host whilst diabetes is an established risk factor for periodontitis. Diabetes has been shown to alter the subgingival microbiota into distinct microbial communities which favours the shift towards disease. It is these very distinct subgingival microbiota that are believed to contribute to the high prevalence and severity of periodontitis in diabetic patients. This dysbiotic microbiota constitute traditional periodontal pathogens which include among others the red complex triad (Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia), Aggregatibacter actinomycetemcomitans, the orange complex (Fusobacterium nucleatum, Prevotella intermedia etc.) and other emerging pathogens such as Fa that were previously unrecognised as role players in the pathogenesis of periodontitis. Fa is an asaccharolytic anaerobic gram-positive rod (AAGPR) currently considered to be one of the potential drivers of periodontitis progression and worsening through its unique virulence characteristics. Various mechanisms through which Fa contributes to the pathogenesis and severity of periodontitis have been reported. The mechanisms involved in the bidirectional relationship between periodontitis and diabetes are continuously being explored in order to enhance individualised preventative and management approaches in affected patients. This review aims to report on this emerging periodontal pathogen and its capacity to influence dysbiosis within a complex subgingival microbial community; including its potential role in the bidirectional relationship between diabetes and periodontitis. This review will highlight Fa as a potential prognostic indicator for disease worsening, which will help improve management protocols for periodontitis and diabetes.